2009
DOI: 10.1104/pp.109.143867
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Lotus and Arabidopsis Basic Helix-Loop-Helix Proteins Reveals New Players in Root Hair Development    

Abstract: Basic helix-loop-helix (bHLH) proteins constitute a large family of transcriptional regulators in plants. Although they have been shown to play important roles in a wide variety of developmental processes, relatively few have been functionally characterized. Here, we describe the map-based cloning of the Lotus japonicusROOTHAIRLESS1 (LjRHL1) locus. Deleterious mutations in this locus prevent root hair development, which also aborts root hair-dependent colonization of the host root by nitrogen-fixing bacteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 36 publications
2
109
2
1
Order By: Relevance
“…However, although we showed that the genetic components of this gene-regulatory network have been conserved, the detailed patterns of transcriptional regulation within this network remain to be resolved. For example, AtRHD6 and AtRSL1 (class I RSL genes) regulate the expression of AtLRL3 in A. thaliana (13,14), but we could not find evidence that PpRSL genes control PpLRL gene expression in P. patens. If there is a genuine absence of transcriptional regulation between LRL and class I RSL genes in P. patens, then two alternative evolutionary scenarios can be suggested.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…However, although we showed that the genetic components of this gene-regulatory network have been conserved, the detailed patterns of transcriptional regulation within this network remain to be resolved. For example, AtRHD6 and AtRSL1 (class I RSL genes) regulate the expression of AtLRL3 in A. thaliana (13,14), but we could not find evidence that PpRSL genes control PpLRL gene expression in P. patens. If there is a genuine absence of transcriptional regulation between LRL and class I RSL genes in P. patens, then two alternative evolutionary scenarios can be suggested.…”
Section: Discussioncontrasting
confidence: 67%
“…We show here that LRL genes positively regulate the development of the tip-growing rhizoids and caulonema in the moss P. patens. LRL genes also positively regulate the development of root hairs in angiosperms (13)(14)(15). Given that similar proteins control the development of filamentous rooting cells at the plant-soil interface in mosses and angiosperms, we conclude that LRL genes positively regulated the development of tip-growing rooting cells in the common ancestor of mosses and angiosperms that existed sometime before 420 y ago (30).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…PIF-like genes in P. patens also lack the APB motif but contain a putative APA motif (Supplemental Figure 10), suggesting that the APB motif might have been acquired during the course of land plant evolution. The M. polymorpha protein most similar to Mp-PIF, Mapoly0502s0001, was placed in another clade, subfamily XI (Pires and Dolan, 2010), together with At-LRL1, which functions in root hair development (Karas et al, 2009). Neither the APA nor the APB motifs are present in the sequences of the proteins in subfamily XI, supporting the notion that M. polymorpha has only a single PIF transcription factor.…”
Section: Polymorpha Has a Single Pif Transcription Factormentioning
confidence: 55%